If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 13x + 1 = 11x + 8 Reorder the terms: 1 + 13x = 11x + 8 Reorder the terms: 1 + 13x = 8 + 11x Solving 1 + 13x = 8 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 1 + 13x + -11x = 8 + 11x + -11x Combine like terms: 13x + -11x = 2x 1 + 2x = 8 + 11x + -11x Combine like terms: 11x + -11x = 0 1 + 2x = 8 + 0 1 + 2x = 8 Add '-1' to each side of the equation. 1 + -1 + 2x = 8 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 8 + -1 2x = 8 + -1 Combine like terms: 8 + -1 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5

| -5-5x=13-7x | | 2x+7=25 | | A+1-5=-8 | | 129-6x=5x+8 | | 2x+7=-59-9x | | 3(x-2)+5x=1 | | -11-9x=7x+21 | | 16+-6s=12+2s | | -8w+4=36 | | V-2+5=-1 | | 11-7x=166-42x | | 159-4x=32x+19 | | x+4-7x=22 | | 6x+10=-26 | | 6-3x=4(3-x)-6 | | 2+x-2=3 | | 5.1u-6.6=2.4-0.9u | | -2x-x=9 | | 3(x-2)+5x=18 | | 2(j+11)=-5(10-2j) | | 6x+-2+2x=-2+4x+8 | | 9a-1=27 | | 9(a-1)=27 | | -3(b+5)=6 | | -6+2x+3x=29 | | -5(r-30)=10 | | 100+-89x=121 | | -4(n-3)=8 | | -13(g+1)=39 | | 12(-2x+3)-4x+17= | | 2x+11-4x=8x+6x-37 | | 12.50+1.50x=4x | | -20=-5(a+7) | | v-25=-27 | | -3y+15-y= | | 2b+4=18-9b | | -3y-y= | | 5(x+1)-4x=x-5 | | 12=3(m+5) | | 5x+2(4-x)=-10 | | 9(6+r)=27 | | -23=7+5x | | 10x+5+0=-2x+-3x+80 | | 5(x+4)=25 | | -26=5(4-d) | | 3m+1=-5+m | | 9(r-6)=27 | | 3k-9=27 | | -38=5(2-v) | | 1x+5=x-5 | | 0.2x+1.4=3.2 | | -38=-5(2-v) | | 0x+7+5x=2x+30+40 | | F+4=-6 | | -4y=0 | | 11x=10x-17 | | (3x-5)+4x=6x+(x+2) | | N-42860=-1286 | | -11+10x+11+-33=x+2x+100 | | x+13=21 | | -7q+2=11q-8q | | 1+4x=21 | | 10+20x+-10=15x+-5x+90 | | -11x=-121 | | 3k+14=k |